Personal views of aging in midlife and older age: the role of personality - Carbone, Elena; Sella, Enrico; Signori, Diletta; Borella, Erika (Frontiers in Psychology, 2024)
Introduction: Personal views of aging (VoA) reflect individuals' perceptions, attitudes, and expectations regarding their aging selves. The present cross-sectional study was aimed at examining whether personality traits, as defined by the Big Five model, are associated with different VoA concepts related to both subjective age and awareness of age-related gains and losses in midlife and older age. Materials and methods: A sample of 224 participants aged 46 to 85 years reported their felt age and completed the Awareness of Age-Related Change (AARC) questionnaire, assessing perceptions of age-related gains (AARC-Gains) and losses (AARC-Losses) in various functioning domains, as well as the short version of the Big Five Inventory. Results: Linear regression models showed that Openness contributed to explain youthful subjective age. Extraversion explained higher AARC-Gains scores, whereas Emotional Stability, along with younger chronological age and perceiving better self-rated health, contributed to explaining lower AARC-Losses scores. Discussion: These findings confirm the relationship between personality traits and personal VoA. They further suggest that such an association varies depending on the VoA measure considered. They underscore the importance of considering personality among those individual characteristics capable of shaping personal VoA, with implications for the development of tailored interventions and the understanding of the underlying mechanisms linking personal VoA to health and longevity outcomes in midlife and older age.